A New Scientometric Database of Scientific Publications in Brazilian International Relations Journals (1997-2021) - Rocha, Pedro Diniz [UNESP] (Pontifícia Universidade Católica do Rio de Janeiro, Instituto de Relações Internacionais, 2023)
In this article, we present a new dataset covering metadata on 14 Brazilian International Relations (BIR) journals and more than 5000 articles published between 1997 and 2021. We collected the data by harvesting the journals’ public web pages via web scraping and later cleaned and structured the information in a rectangular format. A complete understanding of the International Relations field in Brazil requires a deep analysis of the ecosystem of IR academic journals and engaging explicitly and exclusively with scientific articles published in such venues. But, as of today, scientometric analysis covering BIR is rare and limited, as primary indexing sources and popular databases do not fully cover Brazilian International Relations journals. By presenting and publishing the dataset we aim to overcome such a barrier and encourage further scientometric studies in the country.

Neste artigo, apresentamos um novo conjunto de dados que abrange metadados de 14 periódicos de Relações Internacionais do Brasil (BIR) e mais de 5.000 artigos publicados entre 1997 e 2021. Coletamos os dados coletando as páginas públicas da revista via web scraping e posteriormente limpas e estruturou as informações em formato retangular. A compreensão completa da área de Relações Internacionais no Brasil exige uma análise profunda do ecossistema de periódicos acadêmicos de RI e engajamento explícita e exclusiva com artigos científicos publicados nesses locais. Mas, atualmente, a análise cienciométrica cobrindo BIR é rara e limitada, pois as fontes primárias de indexação e as bases de dados populares não cobrem integralmente os periódicos brasileiros de Relações Internacionais. Ao apresentar e publicar o conjunto de dados, pretendemos superar essa barreira e incentivar mais estudos cienciométricos no país.
Uma nova base cienciométrica de publicações científicas em Revistas Brasileiras de Relações Internacionais (1997-2021)
Keywords: International Relations; Brazil; metadata; web scraping; bibliometrics; Relações Internacionais; Brasil; metadados; raspagem da web; bibliometria